Challenges to conducting adolescent HIV prevention services research with court-involved youth. (December 2017) - Tolou-Shams, Marina; Harrison, Anna; Conrad, Selby M.; Johnson, Sarah; Brown, Larry K.
Abstract: Multiple assessment studies demonstrate that juvenile offenders are at increased risk for contracting HIV and other STIs relative to their non-offending counterparts. Such data are used to support the implementation of adolescent HIV prevention interventions within the juvenile justice system. Despite the compelling data related to high rates of unprotected sexual activity, pregnancy, STIs, substance use and psychiatric symptoms, there are very few empirically supported HIV prevention interventions for this adolescent subgroup. Using our experience conducting HIV prevention research studies with court-involved, non-incarcerated (CINI) youth we identify salient and unique challenges to consider when conducting HIV prevention intervention research with this population. Obstacles to consider include lack of "buy-in" and engagement from justice staff and families about the need for youth sexual health promotion and HIV prevention services and logistical barriers (time, transportation, space) related to conducting intervention research with a community-based sample of justice-involved youth. We consider these various challenges and provide recommendations for researchers on how to overcome barriers to continue to develop evidence-based HIV prevention services for communities of youth in need.